Facing the challenges of the humanities and social sciences: the IIUM Way - Hasan, Md. Mahmudul (2017)
There is a strong commonality between Islam and the humanities and social sciences in the sense that both encompass heterogeneous aspects of human life and its conditions and experiences. However, divergence between these two entities is palpable, as the conventional humanities and social sciences look at life from a secular perspective. Some disciplines of the humanities and social sciences also concern the origin of life, its purposes on earth and its final destination. If answers to such questions and associated life lessons are derived from Humanistic concepts and secular knowledge systems, and the worldview based on divine revelation is ignored, the inevitable consequences of the “pursuit of [such] knowledge” will be “a deviation from the truth.” Given the dominance of secular and colonialist philosophies in the humanities and social sciences, they influence in a very subtle and complex way the worldview, attitudes, beliefs, and even values of their recipients. Thus, since the incursion of the modern, western knowledge system in the Muslim world in the colonial period, education in Muslim societies has undergone a paradigm shift, as a result of which most graduates maintain a western orientation in the style and delivery of their academic practices as well as in the various dimensions of their socio-cultural life. As there is much in western education which Muslims can accept without any qualms, it also promotes aspects which they are morally and religiously obligated to reject. However, as regards western philosophies and ideas contained in the humanities and social sciences, Muslims are polarized. One group uncritically accepts the entire bulk of the humanities and social sciences, while the other rejects outright western sciences in their totality. Both these mutually exclusive approaches among Muslims, especially to the humanities and social sciences, are deleterious and debilitating. Based on this observation, this paper will discuss ways of facing the challenges of the humanities and social sciences in such a Muslim academic setting as International Islamic University Malaysia (IIUM). It will also dilate upon the imperatives of the (Islamic) scholars of the humanities and social sciences for facing their challenges successfully.